SEKTOR INFORMAL SEBAGAI PILAR KETAHANAN PANGAN DALAM MENOPANG EKONOMI KERAKYATAN - RINA NURHAYATI RINA NURHAYATI (EKBIS (Ekonomi & Bisnis), 2018)
This research was conducted through a qualitative method approach with a descriptive case study that describes the informal sector as a pillar of food security in supporting the social economy. Through informal businesses in this global competition, the fact that businesses in the community canteen trader is able to survive in the midst of heavy and hard to face the era of the Asean Economic Community (AEC) by the inclusion of a wide range of formal business sectors on a large scale. Many investors into Indonesia with the ease of getting the facility. In the end, small businesses in the informal sector with a wide range of creative product capable of competing creative ideas continue to be developed along with the ability and willingness to be applied in the work of innovative, to be able to continue to live better. This is the central pillar of food security which occur in supporting community economy competitive.